DETERMINATION OF FLOOD RISKS IN THE MORUMBI STREAM BASIN, PIRACICABA-SP - Novaes, Camila Pontine [UNESP]; Perusi, Maria Cristina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2016)
In Brazil can be identified several environmental issues, one of the most recurrent are the floods. This phenomenon is concentrated in urban areas, in which the urbanization process has a key role being directly related to pollution of rivers, partial decimation and even total of the vegetation, especially the riparian, despite the current legislation, and intense sealing soil, among others factors, causing impacts on the environment. Therefore, this paper aimed to determine the risk degree of floods in Morumbi stream basin, located in Piracicaba/SP, where floods occur every year affecting the population, such as in the case of floods in the rivers Piracicaba and Piracicamirim, historically documented. For this, it was used the methodology proposed by Oliveira and Robaina (2004), which considers three variables: natural susceptibility; urban pattern; accident registrer (events), when crossed lead to determine the risk degree. The risk degree resulted in the Risks Grade III - Moderate, in which the area is presented with natural susceptibility and is occupied with Urban High Standard with event records and the Risk Grade IV Low, when the High Standard occupied area features natural susceptibility and has no record of events occurring.
Keywords: floods; risk degree; urbanization; natural susceptibility; irregular occupation